2021
DOI: 10.1111/1467-8268.12502
|View full text |Cite
|
Sign up to set email alerts
|

Do remittances moderate financial development–informality nexus in North Africa?

Abstract: The prevalent informality and sheer size of international remittances characterize the North African countries. This study primarily aims at investigating how remittances moderate the effects of financial development on the informal economy in North African countries. Employing pool mean group (PMG)/panel ARDL approach and a balanced panel data set over the period 1980-2015, we find that remittances moderate the negative relationship between financial development and informal economy. This finding suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…First, given that the nexus between inequality and remittances is inverse U-shaped, policymakers in the Philippines should pinpoint the fundamental causes of why remittances initially exacerbate income inequality and introduce relevant policies accordingly. Second, as argued in Akçay and Karabuluto glu (2021), confirming that remittances ameliorate income inequality after a threshold level is reached, authorities should consider policies and strategies that will promote remittance inflows, such as (1) reducing the transfer cost of remittances, (2) reducing the risks involved in remittances transfers and, (3) improving the financial literacy of remittance-recipient families. Third, policymakers should continue their policies to ease financial constraints, reduce credit market imperfections, and reduce the cost of obtaining a passport and red tape, which will amplify the emigration opportunities for low-income families.…”
Section: Discussionmentioning
confidence: 99%
“…First, given that the nexus between inequality and remittances is inverse U-shaped, policymakers in the Philippines should pinpoint the fundamental causes of why remittances initially exacerbate income inequality and introduce relevant policies accordingly. Second, as argued in Akçay and Karabuluto glu (2021), confirming that remittances ameliorate income inequality after a threshold level is reached, authorities should consider policies and strategies that will promote remittance inflows, such as (1) reducing the transfer cost of remittances, (2) reducing the risks involved in remittances transfers and, (3) improving the financial literacy of remittance-recipient families. Third, policymakers should continue their policies to ease financial constraints, reduce credit market imperfections, and reduce the cost of obtaining a passport and red tape, which will amplify the emigration opportunities for low-income families.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Njangang et al (2020) found that financial development is instrumental in reducing the shadow economy in Sub‐Saharan Africa while Akçay and Karabulutoğlu (2021) found that international remittances modulate the financial development–shadow economy nexus in North African countries. Moreover, given that the share of the shadow economy moves in the opposite direction to the formal economy, improving the latter's productivity shrinks the shadow economy (Elgin, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kakhkharov and Rohde (2020), based on dynamic GMM estimation, found a positive impact of remittances on financial development. More recently, Akçay and Karabulutolu (2021) investigated the nexus between remittances and financial development for a panel of North African countries. Their findings show that remittances strengthen financial development and moderate the negative relationship between financial development and the informal economy.…”
Section: Introductionmentioning
confidence: 99%